A Role for miR-145 in Pulmonary Arterial Hypertension: Evidence From Mouse Models and Patient Samples - Caruso, Paola; Dempsie, Yvonne; Stevens, Hannah C.; McDonald, Robert A.; Long, Lu; Lu, Ruifang; White, Kevin; Mair, Kirsty M.; McClure, John D.; Southwood, Mark; Upton, Paul; Xin, Mei; et al. (Circulation research, 2012)
RATIONALE:Despite improved understanding of the underlying genetics, pulmonary arterial hypertension (PAH) remains a severe disease. Extensive remodeling of small pulmonary arteries, including proliferation of pulmonary artery smooth muscle cells (PASMCs), characterizes PAH. MicroRNAs (miRNAs) are noncoding RNAs that have been shown to play a role in vascular remodeling. OBJECTIVE:We assessed the role of miR-145 in PAH. METHODS AND RESULTS:We localized miR-145 in mouse lung to smooth muscle. Using quantitative PCR, we demonstrated increased expression of miR-145 in wild-type mice exposed to hypoxia. PAH was evaluated in miR-145 knockout and mice treated with anti-miRs via measurement of systolic right ventricular pressure, right ventricular hypertrophy, and percentage of remodeled pulmonary arteries. miR-145 deficiency and anti-miR–mediated reduction resulted in significant protection from the development of PAH. In contrast, miR-143 anti-miR had no effect. Furthermore, we observed upregulation of miR-145 in lung tissue of patients with idiopathic and heritable PAH compared with unaffected control subjects and demonstrated expression of miR-145 in SMC of remodeled vessels from such patients. Finally, we show elevated levels of miR-145 expression in primary PASMCs cultured from patients with BMPR2 mutations and also in the lungs of BMPR2-deficient mice. CONCLUSIONS:miR-145 is dysregulated in mouse models of PAH. Downregulation of miR-145 protects against the development of PAH. In patient samples of heritable PAH and idiopathic PAH, miR-145 is expressed in remodeled vessels and mutations in BMPR2 lead to upregulation of miR-145 in mice and PAH patients. Manipulation of miR-145 may represent a novel strategy in PAH treatment.